Distribution changes of Ormosia microphylla under different climatic scenarios - Pan Huang; Yaqin Xiao; Yurong Sun; Huihua Huang; Zhiwei Gong; Yingfang Zhu (Scientific Reports)
Abstract Ormosia microphylla is a nationally prioritized wild plant in China but effects of likely future climate change have been poorly studied. Here distribution data of O. microphylla and environmental data with an optimized MaxEnt maximum entropy model were used to predict potentially suitable areas under current and future climate scenarios. The results showed that with future climate warming, the total area suitable for O. microphylla might gradually increase. In the three future periods (2030s (2021–2040), 2050s (2041–2060) and 2090s (2081–2100)), the medium and high suitable areas under different climate scenarios generally showed an expanding trend, while the low suitable areas mostly showed a decreasing trend. At the same time, the potential suitable areas for O. microphylla in China have shown a certain degree of migration trend towards higher latitudes in the north and northwest, as well as a trend towards higher altitudes. The research results will provide data support for the protection of germplasm resources and the development of artificial cultivation techniques for O. microphylla, and provide a theoretical basis for the protection of other rare and endangered plants.